2019
DOI: 10.3847/1538-4357/ab2052
|View full text |Cite
|
Sign up to set email alerts
|

Nonparametric Star Formation History Reconstruction with Gaussian Processes. I. Counting Major Episodes of Star Formation

Abstract: The star formation histories (SFHs) of galaxies contain imprints of the physical processes responsible for regulating star formation during galaxy growth and quenching. We improve the Dense Basis SFH reconstruction method of Iyer & Gawiser (2017), introducing a nonparametric description of the SFH based on the lookback times at which a galaxy assembles certain quantiles of its stellar mass. The method uses Gaussian Processes to create smooth SFHs that are independent of any functional form, with a flexible num… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
117
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 127 publications
(121 citation statements)
references
References 144 publications
2
117
2
Order By: Relevance
“…Carnall et al (2018) study a sample of quiescent galaxies from UltraVISTA at 0.25 < z < 3.75 and find that the majority of galaxies quench on timescales of ∼ 0.4τ H , with a rising set of galaxies towards the lower redshift portion of their observations with quenching timescales ∼ 0.6τ H . Iyer et al (2019) analysed a sample of CANDELS galaxies at 0.5 < z < 3.0 and found that ∼ 15 − 20% of galaxies showed evidence for multiple strong episodes of star formation, with the median timescale separating multiple peaks to be ∼ 0.4τ H , which matches the predictions using cosmoto the PSDs of individual galaxy SFHs over time. This assumption is explored in detail in Wang & Lilly (2020a).…”
Section: Observational Constraints In Psd Spacesupporting
confidence: 55%
See 4 more Smart Citations
“…Carnall et al (2018) study a sample of quiescent galaxies from UltraVISTA at 0.25 < z < 3.75 and find that the majority of galaxies quench on timescales of ∼ 0.4τ H , with a rising set of galaxies towards the lower redshift portion of their observations with quenching timescales ∼ 0.6τ H . Iyer et al (2019) analysed a sample of CANDELS galaxies at 0.5 < z < 3.0 and found that ∼ 15 − 20% of galaxies showed evidence for multiple strong episodes of star formation, with the median timescale separating multiple peaks to be ∼ 0.4τ H , which matches the predictions using cosmoto the PSDs of individual galaxy SFHs over time. This assumption is explored in detail in Wang & Lilly (2020a).…”
Section: Observational Constraints In Psd Spacesupporting
confidence: 55%
“…As observations continue to grow in quality, techniques that reconstruct the SFHs from observations are able to extract more robust constraints on the SFHs of individual galaxies and ensembles (Pacifici et al 2012;Smith & Hayward 2015;Leja et al 2017;Carnall et al 2018;Iyer et al 2019). We now approach the point where we can compare observational distributions of galaxy SFHs to those from simulations to obtain constraints on intermediate-to-long timescales.…”
Section: Take Down Policymentioning
confidence: 99%
See 3 more Smart Citations